PENERAPAN COMPETITIVE INTELLIGENCE PROGRAM (CIP) UNTUK MENDUKUNG KEBERHASILAN PADA RITEL - I, DHONY WAHYU (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The competition among the retailers cause the retailer implement competitive intelligence program. The change rapidly of the environment specialty the customer environment caused by increasing technology and culture to be the other support that must have to identify the change of environment. The suitable between the operational decision and the environmental change caused the operational decision which applied by retailer will to be positive responsible from the market environmental, so the existence of the retailer received by the environmental retailer. Being success for the application of competitive intelligence program, retailer have to supply the competitive human resources. The retailer have to has the strong commitment to use the competitive intelligence program. The retailer must choose the application of technologies which support the competitive intelligence program. The information which is resulted by Competitive Intelligence Program to be the key success for the competition strategy for the retailer. The resources which is important to support application of competitive intelligence program are: human resources and technology. Both of them support the sucessfully of application competitive intelligence program at retailers.